DERAJAT VERTEKS GRAF TERHADAP HIMPUNAN VERTEKS - Fauziah Arani; Rolan Pane; Endang Lily (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article  discusses  methods  to  define  the degrees of the  graph  vertex. These  methods include  union, intersection, and  difference  symmetric  from  vertex set. Based on this definition the relation  between the  degrees  of the graph  vertex and  vertexset  is  obtained. An example is given to illustrate the implementation of the methods.